Determinan Pengeluaran Konsumsi Rumah Tangga dan Kemiskinan di Provinsi Sumatera Barat - Agnes Dinda Azhari; Alpon Satrianto (Universitas Negeri Padang, 2026)
Household consumption expenditure and poverty rate are important indicators for assessing societal welfare. This study analyzes the influence of per capita income, number of family members, and education level on household consumption expenditure, as well as the influence of per capita income, education level, and unemployment rate on poverty rate in West Sumatra Province. The data used are district/city panel data for the period 2019–2023, sourced from the Central Statistics Agency (BPS). Data analysis was conducted using the Seemingly Unrelated Regression (SUR) method. The results indicate that in the household consumption expenditure model, all independent variables do not have a meaningful effect. Meanwhile, in the poverty model, per capita income has a unidirectional and meaningful effect, education level has an inversely meaningful effect, and the data do not show evidence that the unemployment rate contributes to changes in the poverty rate. Based on these findings, the government is advised to expand access to education, improve the quality of human resources, and formulate more targeted poverty alleviation policies according to regional characteristics in West Sumatra Province.